A Culture of Savings Solutions for Consumptive Behavior and Care for the Future - Handayani Handayani; Agus Caesario (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
Saving is a simple act that is difficult to do, therefore there needs to be habituation from an early age, and the support of many parties. The thing that must be realized in saving is the long-term benefits, for example it is useful for the cost of education, health, business capital, old age life, and so on. The most important thing from the culture of saving is to form a caring attitude towards excessive life, especially in terms of consumption. This activity aims to increase public knowledge about the benefits of saving for future life. The dynamics of life often give birth to many problems and need money as a solution, by saving these things can be overcome. This community service activity is carried out with educational methods and games. The result of this activity is to motivate the participants to be able to put aside the money given by their parents and not to overspend it. So that two attitudes are built at once, namely diligent saving and not consumptive.